Applications of Sobolev Lattice Cubature Formulas - Ramazanov, Marat; Rakhmatullin, Dzhangir (Eurasian Mathematical Journal, 2013)
In this note we discuss new theoretical results on Sobolev lattice formulas and applications to programmes for multi-dimensional approximate integrating and solving integral equations.